Atomic Layer Deposition of Sb2Te3/GeTe Superlattice Film and Its Melt‐Quenching‐Free Phase‐Transition Mechanism for Phase‐Change Memory. Issue 50 (3rd November 2022) - Yoo, Chanyoung; Jeon, Jeong Woo; Yoon, Seungjae; Cheng, Yan; Han, Gyuseung; Choi, Wonho; Park, Byongwoo; Jeon, Gwangsik; Jeon, Sangmin; Kim, Woohyun; Zheng, Yonghui; Lee, Jongho; et al.
Abstract: Atomic layer deposition (ALD) of Sb2 Te3 /GeTe superlattice (SL) film on planar and vertical sidewall areas containing TiN metal and SiO2 insulator is demonstrated. The peculiar chemical affinity of the ALD precursor to the substrate surface and the 2D nature of the Sb2 Te3 enable the growth of an in situ crystallized SL film with a preferred orientation. The SL film shows a reduced reset current of ≈1/7 of the randomly oriented Ge2 Sb2 Te5 alloy. The reset switching is induced by the transition from the SL to the (111)‐oriented face‐centered‐cubic (FCC) Ge2 Sb2 Te5 alloy and subsequent melt‐quenching‐free amorphization. The in‐plane compressive stress, induced by the SL‐to‐FCC structural transition, enhances the electromigration of Ge along the [111] direction of FCC structure, which enables such a significant improvement. Set operation switches the amorphous to the (111)‐oriented FCC structure. Abstract : An in situ crystallized Sb2 Te3 /GeTe superlattice film is grown by atomic layer deposition on the planar and sidewall memory cell, showing a significantly decreased reset current compared with the homogeneously mixed alloy. The in‐plane compressive stress and effective electromigration of the Ge atoms induce a melt‐quenching‐free amorphization mechanism.